Learning Islamic Religious Education with Muhammadiyah Nuances in Universities - Badriah, Siti; Handayani, Dita; Mahyani, Aang; Arifin, Bambang Syamsul (Pascasarjana Universitas KH. Abdul Chalim, 2023)
Islamic Religious Education learning has not achieved maximum goals, and many sides of knowledge that must be improved. Universitas Muhammadiyah Bandung (UMB) is a university that has a unique curriculum for learning Islamic Religious Education by adjusting the central curriculum. This paper aims to describe the learning of Islamic Religious Education at Muhammadiyah Bandung University in developing Islamic Religious Education learning in Indonesian universities. The method used in this research uses qualitative methods through data collection techniques carried out by observation, interviews, literature studies, and documentation. The results showed that the Muhammadiyah University of Bandung has a unique model of learning Islamic Religious Education called Al Islam and Kemuhammadiyahan (AIK). This model was developed to solve the problem of learning Islamic Religious Education that is common in universities in Indonesia. Therefore, the AIK model at the Muhammadiyah University of Bandung can be an alternative to Islamic Education learning in other universities in Indonesia.